An Analysis of Student Difficulties in Mathematics Learning in terms of Student Mathematical Connection Ability on Pythagoras Theorem - Sholeha, Viona Aida; Risnawati, Risnawati; Habibullah, Habibullah (Prisma Sains : Jurnal Pengkajian Ilmu dan Pembelajaran Matematika dan IPA IKIP Mataram, 2021)
This research aimed to describe student difficulties in mathematics learning in terms of student mathematical connection ability on Pythagoras theorem. This research was a qualitative descriptive research with case study design. The research subjects were 18 the IX grade students, then reduced to 5 students and purposive sampling technique was used in this research. Triangulation data such as mathematical connection ability and difficulties of mathematic learning tests and interview were used for collecting the data.Â The data were analyzed by Miles and Hubermen techniques including three stages: reduction, presentation, and conclusion/verification. The findings of this research showed that, each respondent has different difficulties at each mathematical connection ability level; (1) The subject (very high) mathematical connection ability level did not have problem with all indicators of difficulties in mathematics learning; (2) The subject (high) mathematical connection ability level had associations or visual-motor combination; (3) The subject (medium) mathematical connection ability level had associations or visual-motor combination and difficulties in recognizing and using symbols; (4) The subject (low) mathematical connection ability level had little spatial disruption, association or visual-motor combination, and little difficulties in recognizing and using symbols; (5) The subject (very low) mathematical connection ability level had spatial disruption, association or visual-motor combination, and difficulties in recognizing and using symbols